Preoperative blood pressure targets and effect on hemodynamics in pheochromocytoma and paraganglioma - Randi Ugleholdt; Åse Krogh Rasmussen; Pernille A H Haderslev; Bjarne Kromann-Andersen; Claus Larsen Feltoft (Endocrine Connections, 2022)
Patients with pheochromocytoma and paraganglioma (PPGL) are treated with α-adrenoceptor antagonists to improve peroperative hemodynamics. However, preoperative blood pressure targets differ between institutions. We retrospectively compared per- and postoperative hemodynamics in 30 patients with PPGL that were pretreated with phenoxybenzamine aiming at different blood pressure targets at two separate endocrine departments. All patients were subsequently undergoing laparoscopic surgery at Department of Urology, Herlev University hospital. Fourteen patients were treated targeting to symptomatic and significant orthostatic hypotension and 16 patients to a seated blood pressure below 130/80 mmHg. As a control group, we included 34 patients undergoing laparoscopic adrenalectomy for other reasons. The group titrated to orthostatic hypotension required a higher dose of phenoxybenzamine to achieve the blood pressure target. This group had less intraoperative systolic and diastolic blood pressure fluctuation (Mann–Whitney U test; P < 0.05) and less periods with heart rate above 100 b.p.m. (Mann–Whitney U test; P = 0.04) as compared to the group with a preoperative blood pressure target below 130/80 mmHg. Peroperative use of intravenous fluids were similar between the two groups, but postoperatively more intravenous fluids were administered in the group with a target of ortostatism. Overall, the control group was more hemodynamic stable as compared to either group treated for PPGL. We conclude that phenoxybenzamine pretreatment targeting ortostatic hypotension may improve peroperative hemodynamic stability but causes a higher postoperative requirement for intravenous fluids. Overall, PPGL surgery is related to greater hemodynamic instability compared to adrenalectomy for other reasons.